Proceedings of the 25th International Conference on World Wide Web 2016
DOI: 10.1145/2872427.2874813
|View full text |Cite
|
Sign up to set email alerts
|

User Fatigue in Online News Recommendation

Abstract: Many aspects and properties of Recommender Systems have been well studied in the past decade, however, the impact of User Fatigue has been mostly ignored in the literature. User fatigue represents the phenomenon that a user quickly loses the interest on the recommended item if the same item has been presented to this user multiple times before. The direct impact caused by the user fatigue is the dramatic decrease of the Click Through Rate (CTR, i.e., the ratio of clicks to impressions). In this paper, we prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 25 publications
0
13
1
Order By: Relevance
“…In addition to providing patients with educational training on using eHealth technology, an accompanying support system that enhances user experience is integral to sustain patient adoption of eHealth interventions (eg, responsive helpdesk offering prompt guidance, and health monitoring through a combination of human and machine feedback given in a timely manner). Positive user experience can alter patients' perception and their innate attitude towards the use of technology, but it is unclear whether the factor related to user experience and/or TR trait is associated with “user fatigue,” a common phenomenon observed with eHealth interventions 16 …”
Section: Discussionmentioning
confidence: 99%
“…In addition to providing patients with educational training on using eHealth technology, an accompanying support system that enhances user experience is integral to sustain patient adoption of eHealth interventions (eg, responsive helpdesk offering prompt guidance, and health monitoring through a combination of human and machine feedback given in a timely manner). Positive user experience can alter patients' perception and their innate attitude towards the use of technology, but it is unclear whether the factor related to user experience and/or TR trait is associated with “user fatigue,” a common phenomenon observed with eHealth interventions 16 …”
Section: Discussionmentioning
confidence: 99%
“…entertainment gratifications). In this case, the user needs to search for new, different content [12,17]. This phenomenon of having to make adjustments based on situational factors is very similar to the theory of mood management [34].…”
Section: Rq3mentioning
confidence: 91%
“…At the same time, some studies have focused on the media fatigue behaviors of news platform users. Ma H et al [25] demonstrated how statistics analyzing user fatigue could be incorporated into the ranking algorithms for personalized recommendations to reduce the impact of user fatigue. Through our investigation of the current works, as far as we know, no scholars have researched the push strategies of mainstream value information for Chinese news aggregation platforms.…”
Section: Related Workmentioning
confidence: 99%